The Infringement of the Author's Moral Rights In the Perspective of Making Spatial Copies of Works In Formats Accessible to People with Disabilities - Bober-Kotarbińska, Anna (PRAWO i WIĘŹ, 2022)
The catalogue of copyright exceptions and limitations that allow the making of copies and exchanges of works in formats accessible to people with disabilities is oneof the greatest achievements of the modern copyright system. The creation of such a catalogue was not only a response to the needs of persons with disabilities but alsoa signal for the further development of digital technologies to assist persons with disabilities to participate in society on an equal and non-discriminatory basis. Nevertheless, progress in the field of new digital technologies supporting the transformation of the content of works into accessible formats – especially as regards the production of spatial forms – has not been properly systematised within the international law, which may result in infringementsof authors’ moral rights. The author points to the legal grounds for transforming works into spatially accessible formats and the resulting potential infringements of the original work author’s moral rights.